Absolute, reflection and speculative truth - Gutiérrez Cuartango, Román (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
What could be called «the postmodern situation» is the result of the metaphysical assumption according to which being and reality are constructed discursively. However, when you try to make said «truth» effective, you immediately experience the limits of power and management: there is what is subtracted and is absolute. For example: the being evades reflection. What’s more: it is only operational if you lose it. Something similar happens to existence in relation to contingent facticity. Philosophy is renewed in our time by once again facing, in the conditions of great skepticism regarding the requirement of foundation or sufficient reason, the need for speculative thought capable of addressing the absolute.